PENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN MEDIA LAGU PADA SISWA KELAS V - Sari, Aminah (Universitas Negeri Padang, 2014)
Abstract :This research was conducted based on the facts indicating that the teathers did not yet use media in the learning process, and they did not totally guide and lead the students. This was a Classroom Action Research which applied both qualitative and quantitative data. The data gathered were the result of observations in pre-writing phase, whilst-writing phase and post-writing phase. The result of the research revealed that in cycle I meeting I, the students’ average score in pre-writing was 59, in whilst-writing was 69 and in post-writing was 69. In cycle I meeting II, their average score in pre-writing was 71, in whilst-writing was 73 and in post-writing was 74. In cycle II, the students’ average score in pre-writing was 87, in whilst-writing was 84 and in post-writing was 90. Key terms : poetry writing, song, Elementary School Students